2015
DOI: 10.1124/jpet.115.227066
|View full text |Cite
|
Sign up to set email alerts
|

New Multi-target Antagonists of  1A-,  1D-Adrenoceptors and 5-HT1A Receptors Reduce Human Hyperplastic Prostate Cell Growth and the Increase of Intraurethral Pressure

Abstract: Benign prostatic hyperplasia (BPH) is characterized by stromal cell proliferation and contraction of the periurethral smooth muscle, causing lower urinary tract symptoms. Current BPH treatment, based on monotherapy with a 1A -adrenoceptor antagonists, is helpful for many patients, but insufficient for others, and recent reports suggest that stimulation of a 1D -adrenoceptors and 5-hydroxytryptamine (serotonin) (5-HT) 1A receptors contributes to cell proliferation. In this study, we investigated the potential o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 69 publications
3
17
0
Order By: Relevance
“…In our previous paper (7), we detailed the in vitro and in vivo pharmacodynamics properties of LDT5 that support our hypothesis of a multi-target antagonism for a dual effect in BPH treatment. Here, we report data addressing the drug-likeness and safety of our elected compound.…”
Section: Introductionsupporting
confidence: 58%
See 3 more Smart Citations
“…In our previous paper (7), we detailed the in vitro and in vivo pharmacodynamics properties of LDT5 that support our hypothesis of a multi-target antagonism for a dual effect in BPH treatment. Here, we report data addressing the drug-likeness and safety of our elected compound.…”
Section: Introductionsupporting
confidence: 58%
“…The concentration of LDT5 used in these assays (0.5 µM) was chosen according to the typically low concentrations (1–5 µM) of test compound used for incubation to ensure the linearity of enzymatic reaction, but higher than its putative clinically relevant concentration since it is 250–2500 times higher than the affinity for its main target receptors (7). From these data (Figure 2), we can conclude that LDT5 is stable in human liver microsomes (half-life >30 min; intrinsic clearance <0.6 mL·min -1 ·g liver -1 ) and hepatocytes (half-life 120 min; intrinsic clearance <0.2; 0.22 mL·min -1 ·g liver -1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we speculated that most effects of 8-OH-DPAT and WAY-100635 are exerted on the central level rather than on the peripheral level because the intrathecal or intracerebroventricular injections exert excitatory or inhibitory effects, respectively, on micturition reflex activity (17,19,21,37). However, a direct effect of the 5-HT 1A receptor on urethral smooth muscles cannot be excluded because a recent study reported that a 5-HT 1A receptor agonist can modulate the isometric contraction in isolated urethral smooth muscle strips prepared from rats (24). Nevertheless, verification of this assumption is warranted in future studies.…”
Section: Effects Of 8-oh-dpat (03 Mg/kg Iv) and Way-100635 (01 Mg/kmentioning
confidence: 95%